Description of burrowing behaviour of the pipefish Syngnathus abaster Risso, 1827 in the Ria Formosa lagoon, Portugal - Mueller, C. (2016)
Pipefish are generally associated with seagrass habitats, which they mimic in colour, shape and behaviour (Howard & Koehn, 1985), using them as hideouts, nursery and feeding grounds (Franco, Franzoi, Malavasi, Riccato, & Torricelli, 2006; Sundin, Jacobsson, Berglund, & Rosenqvist, 2011; Teixeira & Musick, 1995; Vincent, Berglund, & Ahnesjö, 1995). Pipefish often coexist sympatrically in the same bed with seahorses by partitioning their habitat according to their morphology, mobility and foraging techniques (Howard & Koehn, 1985; Kendrick & Hyndes, 2003).